ROCK CLIMBING AS A HEALTH-PROMOTING ACTIVITY: BENEFITS AND RISKS ACROSS POPULATIONS - Zuzanna Perlicka,; Tomasz Antczak,; Monika Gajda-Bathelt,; Monika Dąbek,; Katarzyna Jania,; Karolina Smolińska,; Paulina Sadkowska,; Julia Kulczycka,; Weronika Popow,; Michał Ciołkosz, (International Journal of Innovative Technologies in Social Science, 2025)
Rock climbing has been steadily gaining popularity worldwide, particularly after its inclusion in the Olympic Games in 2020. As a physically and mentally demanding activity, it uniquely combines strength, endurance, balance, coordination, and problem-solving. This review aims to explore the physical and mental health benefits of recreational rock climbing, with a focus on outdoor settings, as well as the associated risk of injury. Current evidence indicates that climbing can enhance muscular strength, cardiovascular fitness, and body composition, especially among youth and young adults. Additionally, it has been linked to psychological benefits such as improved mood, stress relief, and greater overall well-being. Outdoor climbing, in particular, is associated with higher levels of enjoyment and satisfaction compared to indoor activity, which may promote long-term participation. However, climbing also presents a risk of injury, particularly chronic overuse injuries in the upper limbs, with elite climbers experiencing higher injury rates. Despite these risks, the overall findings support the role of rock climbing as a multidimensional, health-promoting activity. Further research is needed to better understand injury prevention and the long-term health impacts of climbing across different populations.